Macrodystrophia lipomatosa - Andrew J. van den Heever (South African Journal of Radiology, 2014)
Macrodystrophia lipomatosa (MDL) is a rare congenital, but non-hereditary, form of localised gigantism of the fingers or toes. The hallmark of the condition is hypertrophy of all mesenchymal elements in the involved region, with a predominance of fibro-adipose tissue. A clinically subtle case of MDL is presented.